TINJAUAN YURIDIS TERHADAP PERUSAHAAN LAYANAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI YANG MENYEBARKAN DATA PRIBADI DEBITUR BERDASARKAN PASAL 32 UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI KEPOLISIAN DAERAH PROVINSI RIAU - Royan Ramadhan; Davit Rahmadan; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Sanctions for violating personal data are contained in Article 48 paragraph 2, which contains: (1) Any person who meets the elements as referred to in Article 32 paragraph 1 shall be sentenced to a maximum imprisonment of 8 years and / or a maximum fine of two billion rupiah. (2) every person who fulfills the elements as meant in Article 32 paragraph 2 is imprisonment for a maximum of 9 years and / or a maximum fine of three billion rupiah. (3) Every person who fulfills the elements as referred to in Article 32 paragraph 3 shall be sentenced to a maximum imprisonment of 10 years and / or a maximum fine of five billion rupiah. The application of criminal sanctions against perpetrators of criminal defamation of customers must actually be reactive to an act, so the focus of criminal sanctions is focused on a person's wrongdoing through the imposition of suffering (so that the person concerned becomes a deterrent). Apart from being aimed at imposing suffering on the perpetrator, criminal sanctions are also a form of condemnation of the perpetrator's actions.This research uses a typology of sociological legal research or what is also called non-doctrinal legal research, which deals more specifically with legal effectiveness. In this study the authors use the nature of descriptive research, because the author describes how Law Enforcement Against Technology-Based Lending and Borrowing Services Companies That Spread Personal Data of Debtors Who Violate Article 32 of Law Number 19 Year 2016 Regarding Information and Electronic Transactions at Polda Riau. The results of the research conducted by the author are, firstly, the implementation of law enforcement on technology-based lending and borrowing services can be more assertive, and the police should also accept all reports from victims while the report has the potential to violate applicable laws and regulations regardless of whether there are still debts, so that people also feel protected by law enforcement officials, and similar incidents will not happen again.Keywords: Fintech – Personal Data – Electronic Transactions